Los pueblos indígenas del Perú y el desafío de la conquista española. Huamanga hasta 1640. Steve Stern. - Ansión, Juan (1988)
Stern's work, solidly based on an extensive archive work, is an exciting reading for those who want to understand something more about these decisive years in the history of the Huamanga region, and also of the country, since the regional perspective is not for the author but a way of understanding the colonial situation as a whole.